Change the map : Impacting the Buddhist world through prayer and action - Durene, Mark (Assemblies of God World Missions, Coppell, TX, 2021)
From the author and publisher : "Change the Map will stir concern and passion in readers' hearts to reach Buddhist people with the gospel message. These pages contain a treasure of the most impactful and instructional experiences of Mark's missionary career, highlighting the spiritual chasm between the Thai spiritual world and God's kingdon and demonstrating the reckless love of God that overcomes each obstacle to bring lost people to Himself. It is Mark's prayer that the Holy Spirit will speak through each story to bring readers to their knees in intercession for Buddhist people and the missionaries who are sharing the gospel with them. May you respond as the Hily Spirit speaks to your heart."
Foreward by James T. Bradford.
Keywords: Missions to Buddhists; Christianity and other religions Buddhism; Buddhism Relations Christianity